Making humor together: phenomenology and interracial humor - Barber, Michael D. (SocietàMutamentoPolitica, 2016)
This paper explains humor through phenomenological concepts and methods. The three major theories of humor: Superiority, Relief, and Incongruity depend on the thwarting of intentional expectations. Since one experiences an incongruity between what is intended and what is actually experienced, the incongruity theory affords the best explanation, but intentionality remains fundamental for all theories. Theorists of humor rightly insist that the enjoyment of humorous incongruity completes the definition of humor, but such enjoyment also depends on a special epoché, usually elicited by the cues of an interlocutor who invites the listener to leap together into the humorous finite province of meaning. In this province, actions and statements, hurtful in everyday life, such as a pie thrown at someone who ducks as the pie hits another, produce laughter. This comic epoché resembles the phenomenological epoché in its distancing from everyday life, and, like the phenomenological epoché, it opens everyday experience to reflection. Although one often experiences and enjoys humor alone, humor is thoroughly intersubjective and more frequently occurs when two persons participate in the humorous epoché together. The opportunities for making humor together are enhanced to the extent the partners differ in their expectations and responses to situations. Those differences, including bodily differences, often result from the complex intersubjective networks, including culture. As in the case of a seemingly solitary activity like reflection, which one learns from others and exercises on one’s own autonomously, one internalizes others’ styles of humor and discovers such internalization through reflection on one’s «because motives». On the basis of these features – intentionality, epoché, and intersubjectivity, the paper concludes by briefly examining an example of interracial humor. Despite the racist character of much interracial humor, the example shows that interracial humor can produce a respectful bonding between representatives of different races who make humor together.